Curriculum Design of Master Program on Islamic Economics in Indonesian, Pakistan, Turkish, and Malaysian Universities - Hamid Fahmy Zarkasyi; Setiawan bin Lahuri; Khoirul Umam; Eko Nur Cahyo (TSAQAFAH, 2016)
This research is aimed at finding the curriculum design of Islamic economic, especially on its epistemological basis, its method of integration and its method of teaching. The object of research is postgraduate program at universities that offer the degree of Islamic Economic. The universities that will be researched represent four outstanding countries that have serious concern on Islamic economic studies. Those universities are International Islamic University Islamabad Pakistan, Istanbul Sabahattin Zaim University, International Islamic University of Malaysia and four Universities of Indonesia i.e. Islamic State University Sunan Kalijaga Yogyakarta, Islamic State University Sunan Ampel, University of Airlangga, and STIE Tazkia. The data will be collected through documentary and interview method. To analyze the data the researchers employs descriptive, compare and contrast, and synthesis method. The curriculum design that includes the vision and mission where epistimological aspects are clearly stated, in most of Islamic economics departments. However, not all departments that state explicity their vision and mission and objective clearly have clear statement on the integration of conventional and Islamic economics. Islamic State University Sunan Kalijaga Yogyakarta, Islamic State University Sunan Ampel, University of Airlangga, STIE Tazkia, and Istanbul Sabbahatain Zaim do not state clearly the vision and mission in relation the program of integration and Islamization. So the epistimological aspect is not taken into serious consideration as the vision and mission of the program. The Universities that clearly state the integration and Islamization are Islamic Science University of Malaysia, International Islamic University of Islamabad, and International Islamic University of Malaysia.